The Interaction Between Morphological Awareness and Word Detection Skills in Predicting Speeded Passage Reading in Primary and Secondary School Chinese Readers - Liu, Duo; Xu, Zhengye; Wang, Li-Chih (Frontiers in Psychology, 2022)
Previous studies suggest that morphological awareness (MA) and word detection skills have facilitating roles in reading fluency; however, it is unknown whether they can interplay with each other in such roles. The present study explored the relationships of MA, word detection, and passage reading fluency across ages. In total, 180 Chinese primary and secondary school students, aged from 8.52 to 15.67 years, completed tasks for these aforementioned capacities. After controlling gender, non-verbal intelligence, and reading ability at the word level, the results showed that the participants with higher scores for MA or word detection performed better in passage reading fluency. However, the predictive effect of word detection on reading fluency became weaker as the children became older. The interaction between MA and word detection was positive in younger children, whereas this interaction tended to be negative for older children. The results demonstrated a dynamic interplay between MA and word detection in contributing to passage reading fluency in Chinese children. While it has a positive interaction with word detection on reading fluency in younger children, MA may become a compensator in older children (e.g., over 14 years old) whose word detection skills are less effective in facilitating fluent reading.